2007
DOI: 10.1890/07-0263.1
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Affect Prey Biomass and Diversity Through Resource Partitioning

Abstract: Consumer presence and nutrient availability can have contrasting and interactive effects on plant diversity. In a factorial experiment, we manipulated two levels of nutrient supply and the presence of two moderately specialized grazers in different combinations (no grazers, two species in monoculture, and both in combination). We tested how nutrients and grazers regulated the biomass of marine coastal epiphytes and the diversity of algal assemblages, based on the prediction that the effect of consumers on prey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…This may have limited the strength of a species complementarity effect by offering limited functional diversity. Grazers from other phyla, such as the crustacean amphipods and isopods, may, for example, offer a greater potential for resource complementarity due to larger differences in feeding mode (Parker et al 1993, Råberg & Kautsky 2007. Secondly, the relatively homogeneous conditions afforded by these artificial pools (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have limited the strength of a species complementarity effect by offering limited functional diversity. Grazers from other phyla, such as the crustacean amphipods and isopods, may, for example, offer a greater potential for resource complementarity due to larger differences in feeding mode (Parker et al 1993, Råberg & Kautsky 2007. Secondly, the relatively homogeneous conditions afforded by these artificial pools (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Where interspecific resource partitioning occurs, for example, increasing species richness will allow a greater proportion of the resource spectrum to be used, potentially enhancing the associated ecosystem process above that of the single best-performing species (e.g. Råberg & Kautsky 2007, Griffin et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in feeding niche among grazers have been demonstrated in several other seagrass and algae systems (Duffy & Hay 1991, Raberg & Kautsky 2007, Jaschinski & Sommer 2008, and there are several reasons to think that similar patterns of predation susceptibility may not be unique to our system. Below, we consider the generality of our predictions by examining patterns in grazer population growth, size, and habitat use that may be relevant to other seagrass systems.…”
Section: Discussionmentioning
confidence: 86%
“…In seagrass systems, invertebrate grazers vary in their feeding rates on microalgae, macroalgae, and seagrasses themselves (Duffy & Hay 1991, Raberg & Kautsky 2007, Jaschinski & Sommer 2008, Hughes et al 2010. Although much less is known about species-specific predation susceptibility, species do vary in ways that may affect their visibility and escape success, such as size, coloring, and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, herbivore traits, especially edibility (predator resistance), grazing efficiency, and feeding guild, are important mediators of multiple predator effects on lower trophic levels (Stachowicz et al 2007). The resulting biomass and species composition of primary producers is ultimately determined by the functional composition of the herbivores combined with nutrient availability (Råberg & Kautsky 2007). Accordingly, it has been shown that the loss of dominant fish predators in the coastal zone of the Baltic Sea has reduced grazing rates on algae by shifting the functional composition of the herbivore community (Eriksson et al 2009, Sieben et al 2011.…”
Section: Introductionmentioning
confidence: 99%